2016
DOI: 10.9790/1959-0504021321
|View full text |Cite
|
Sign up to set email alerts
|

The Body Mass Index and Menstrual Problems among Adolescent Students

Abstract: Menstruation is an important part of female reproductive cycle but menstrual problems in adolescent girls may affect normal life of adolescent and young adult women. Many factors play a role in regularity and flow of menstrual cycle, which include hormonal changes, genetics and body mass index (BMI). Objective: Objective was to assess the relationship between body mass index and menstrual problems. Design: the current study was a cross sectional study carried out between October 2014 to April 2015. Setting: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 17 publications
1
13
0
4
Order By: Relevance
“…Study conducted in adolescent students reported an excessive amount of blood flow and long interval between the menstrual period (14.3%and 28.6% respectively) in obese, compared to those who had normal BMI (13.1% and 20.7% respectively). Meanwhile, students who were overweight (30.0%) were significantly more likely to have short interval between the menstruation compared to those who had normal BMI (10.7%) [16][17][18] . Based on a cross sectional study on Relationship of Menstrual Irregularities to BMI and nutritional status in adolescent girls Dars et al, found that 75.5% girls with BMI 14-24.9 (underweight to normal) had a normal menstrual pattern.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Study conducted in adolescent students reported an excessive amount of blood flow and long interval between the menstrual period (14.3%and 28.6% respectively) in obese, compared to those who had normal BMI (13.1% and 20.7% respectively). Meanwhile, students who were overweight (30.0%) were significantly more likely to have short interval between the menstruation compared to those who had normal BMI (10.7%) [16][17][18] . Based on a cross sectional study on Relationship of Menstrual Irregularities to BMI and nutritional status in adolescent girls Dars et al, found that 75.5% girls with BMI 14-24.9 (underweight to normal) had a normal menstrual pattern.…”
Section: Discussionmentioning
confidence: 99%
“…All sixteen girls with a BMI of 25 -29.9 kg/m2 (overweight) had infrequent cycles 16 . Many studies [17][18][19][20][21] have confirmed that a higher increase in body mass index (BMI) during childhood is related to an earlier onset of puberty. These results were complimentary to an Indian study which concluded that the increase in BMI is significantly associated with pre-menstrual syndrome (p=0.035) 22 .…”
Section: Discussionmentioning
confidence: 99%
“…This can be due to less number of adolescents with high BMI in our study group (24 out of 450; 5.33 %). A statistically significant relationship was found between BMI and severity of premenstrual symptoms including psychological symptoms (anxiety-depression-nervous) by Abdella NHA et al (2016) 11 .…”
Section: Discussionmentioning
confidence: 87%
“…In addition, they showed a significant correlation between the amount of bleeding and body mass index, and heavier hemorrhages cause iron deficiency, which should be compensated for by iron supplementation (30).…”
Section: Discussionmentioning
confidence: 99%